Clinical approach to adnexal masses in adolescence [Ergende adneksiyal kitleye yaklaşım] - (:unkn) unknown (Kare Publishing, 2011)
The adnexal masses in adolescents contain functional and physiologic cystic formations on one end of the spectrum, and serious malignant tumors on the other end. The primary approach should be expectant management for the cysts which are thought to be benign in this spectrum. The most common malignant tumors in this era are germ cell tumors. The principal clinical approach in these tumors is to preserve organs and fertility. In malignant tumors a staging procedure should also be added. On the contrary, in disseminated tumors the primary surgery is cytoreductive or debulking surgery including radical organ extirpations. Post operative therapy is generally cis platin-containing combination chemotherapy. When tailoring management strategies, the development and psychology of the adolescent girls should be greatly considered as well as preserving fertility to be the ultimate aim of the treatment. Taking the subsequent therapy into consideration, a multidisciplinary approach should be the basis of the management of the malignant tumors of the adenexa.
Keywords: Adnexal masses; Adolescent; Diagnosis; Treatment